The Interaction Mechanism and Application Research of Psychological Judgment and Self-Redemption (Journal of research in medical and health sciences, 2026)
With increasingly intense social competition and an accelerating pace of life, individual mental health issues have gradually garnered public attention. This study explores in detail the intrinsic connection and interaction mechanism between psychological judgment and self-redemption, providing an integrated theoretical perspective for understanding the psychological adjustment mechanisms of individuals in adversity. Psychological judgment, as the cornerstone of individual cognition and emotional responses, permeates and profoundly influences the entire process of self-redemption. Accurate psychological judgment helps individuals more precisely identify the core of problems and fosters proactive problem-solving behaviors, thereby facilitating the process of self-redemption. Conversely, erroneous psychological judgment may lead individuals into cognitive biases and emotional distress, thereby hindering their psychological adaptation, development, and self-redemption. Meanwhile, reflection and summarization during the self-redemption process also prompt individuals to revise their psychological judgment methods, forming a virtuous cycle. Through theoretical analysis, combined with empirical research and case studies, this study reveals the complex interaction between psychological judgment and self-redemption. In practical applications, this paper proposes the application of psychological judgment and self-redemption theories in fields such as personal growth, psychological intervention, and organizational management, providing an effective approach to maintaining and improving individual mental health.
Keywords: Psychological judgment; Self-redemption; Mental health; Cognitive process; Practical application